Employees Safety Behavior and Industrial Accident Mitigations: Moderating Role of Safety Management System in the Nigerian Manufacturing Sector - Akinbode James; Olu-Ogunleye Itunu; Bakare Akeem Adewale; Isah Friday Iyaji; Ogunkoya Samuel; Oyabambi Adeniyi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: This study investigates the moderating role of safety management in the perceived nexus between employees' safety behavior and industrial accident mitigations in the Nigerian manufacturing sector. Methods: This research adopted a survey design to gather data for the study with a leading manufacturing firm in Lagos. The sample size was 188, and data were collected using a structured questionnaire. The collected data were analysed statistically (Structural equation model). The Bowen University Teaching Hospital Ethics Committee granted ethical approval for the study. Results: The study established that safety behavior reduces workplace accident rates. It was also found that a well-organized safety management system can lower industrial accidents. Lastly, a safety management system significantly moderates the relationship between safety behavior and industrial accident mitigation. Conclusion: The study concludes that a safety management system determines safety behavior that mitigates industrial accidents. The study emphasized that safety attitude, safety compliance, safety knowledge, environmental control, fire control system, safety instruction equipment, regulatory enforcement, safety training program, and management commitment to safety regulate employees' safety behavior and mitigate spate of industrial accidents in the sector.